Prediction and prevention of Gestational Diabetes: an update of recent literature. (July 2016) - Kennelly, M.A.; McAuliffe, F.M.
Abstract: A diagnosis of Gestational Diabetes (GDM) confers adverse risk to the health of the mother and fetus both in pregnancy and later life. The background rate in pregnancy varies between 2 and 14% with incidences reported to be as high as 40% in obese populations. GDM diagnoses are escalating because of rising numbers of overweight and obesity in the reproductive age group but also because of different screening and diagnostic criteria. Lifestyle modification in those diagnosed with GDM has been proven to be an effective treatment in attenuating the metabolic dysregulation associated with this and potentially avoiding the need for medical therapy with either metformin or insulin. Emerging evidence in previous years suggests lifestyle interventions (dietary ± physical activity and behavior modification) either pre-pregnancy or antenatally may reduce the incidence of GDM. The first trimester is also becoming an important interrogation period for the prediction of many adverse obstetric outcomes including abnormal glucose metabolism. This review outlines the most contemporary evidence on the prediction and non-pharmacological antenatal prevention strategies used for Gestational Diabetes.